The evaluation of integrating english language learning program in islamic boarding school: The CIPP mode - Sari, Yulnada; Padmadewi, Ni Nyoman; Suarcaya, Putu; Utami, IGA Lokita Purnamika; Ramendra, Dewa Putu (Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
One of the challenges in educational places is to make a suitable program, which is expected to help the students to be more active in teaching and learning processes, especially in English class. One of the institutions that provides English programs is Fadhilatul Islmiyah Islamic Boarding School. Then, this study aims to evaluate the English program, namely the Integration of English Language Learning Program. The evaluation uses the CIPP model by Stufflebeam (1971). The study uses a qualitative method with a case study. The participants are five students, two teachers, and a headmaster at Fadhilatul Islmiyah Islamic Boarding School. The data analysis uses thematic analysis from both teacher and student views following context, input, process, and product stages. The context evaluation showed the students' need to learn grammar and vocabulary. Input evaluation found that the curriculum, syllabus, and textbook are designed by the English teacher. Process evaluation found that the teacher used game and role-play strategies to improve student's speaking skills. Lastly, product evaluation is used to determine whether the program is effective or not, and it uses a test. Then, it found that the result of the post-test was higher than the pre-test.